ANALISIS PENERIMAAN PASAR TERHADAP MIE BERBAHAN TEMPE DAN KELOR - Damiati Damiati; Putu indah Rahmawati (JURNAL GASTRONOMI INDONESIA, 2023)
This research aimed to analyze the customer acceptance on healthy noodle made from tempeh and morringga. This noodle is a new innovation to give the market a healthy choice for their consumption. This research was conducted using quantitative methods. The questionnaire was designed using likert scales. researchers gave samples of Mie Pelor to SMK students, lecturers, teachers and parents of students in kindergarten. The object of this research is noodle texture, taste, color. Data then analyzed with descriptive quantitative methods. This research found that  the Pelor Noodle has high quality in term of texture,  taste and color presentation.  Therefore, respondents stated that Mie Pelor was ready to be marketed and believed to be accepted by the market. Most respondents stated that they were ready to buy and recommend Pelor Noodle.